Development and clinical implementation of semi‐automated treatment planning including 3D printable applicator holders in complex skin brachytherapy. Issue 3 (7th January 2020) - Guthier, Christian V.; Devlin, Phillip M.; Harris, Thomas C.; O'Farrell, Desmond A.; Cormack, Robert A.; Buzurovic, Ivan
Abstract : Purpose: High‐dose‐rate brachytherapy (HDR‐BT) is a treatment option for malignant skin diseases compared to external beam radiation therapy, HDR‐BT provides improved target coverage, better organ sparing, and has comparable treatment times. This is especially true for large clinical targets with complex topologies. To standardize and improve the quality and efficacy of the treatments, a novel streamlined treatment approach in complex skin HDR‐BT was developed and implemented. This approach consists of auto generated treatment plans and a 3D printable applicator holder (3D‐AH). Materials and methods: The in‐house developed planning system automatically segments computed tomography simulation images (a), optimizes a treatment plan (b), and generates a model of the 3D‐AH (c). The 3D‐AH is used as an immobilization device for the flexible Freiburg flap applicator used to deliver treatment. The developed, automated planning is compared against the standard clinical plan generation process for a flat 10 × 10 cm 2 field, curved fields with radii of 4, 6, and 8 cm, and a representative clinical case. The quality of the 3D print is verified via an additional CT of the flap applicator latched into the holder, followed by an automated rigid registration with the original planning CT. Finally, the methodology is implemented and tested clinically under an IRB approval. Results: All automatically generated plans were reviewed and accepted for clinical use. For the clinical workflow, the coverage achieved at a prescription depth for the flat 4, 6, and 8 cm applicator was (100.0 ± 4.9)%, (100.0 ± 4.9)%, (96.0 ± 0.3)%, and (98.4 ± 0.3)%, respectively. For auto planning, the coverage was (99.9 ± 0.3)%, (100.0 ± 0.2)%, (100.0 ± 0.3)%, and (100.1 ± 0.2)%. For the clinical test case, the D90 for the clinical workflow and auto planning was found to be 93.5% and 100.29% of the prescribed dose, respectively. Processing of the patient's CT to generate trajectories and positions as well as the 3D model of the applicator took <5 min. Conclusion: This workflow automates time intensive catheter digitizing and treatment planning. Compared to printing full applicators, the use of 3D‐AH reduces the complexity of the 3D prints, the amount of the material to be used, the time of 3D printing, and amount of quality assurance required. The proposed methodology improves the overall treatment plan quality in complex HDR‐BT and impact patient treatment outcomes potentially.